2017
DOI: 10.1002/hon.2463
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between response rates and median progression‐free survival in non‐Hodgkin's lymphoma: A meta‐analysis of published clinical trials

Abstract: Demonstration of clinical effectiveness of a non-Hodgkin's lymphoma (NHL) treatment generally involves determination of progression-free survival (PFS). However, the long evaluation time of PFS limits its utility to make timely decisions in drug development. Therefore, the objective of this analysis was to determine the relationship between response rates and median PFS in NHL. A database was systematically developed from 513 identified NHL trials reported from 1996 to 2015. Potential predictors of the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The CR rate was 35·5% (95% CI 28·0–43·6) with pixantrone + rituximab and 21·7% (95% CI 15·5–28·9) with gemcitabine + rituximab. However, response and survival outcomes do not always correlate in NHL (Lee et al , ; Zhu et al , ; Mangal et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The CR rate was 35·5% (95% CI 28·0–43·6) with pixantrone + rituximab and 21·7% (95% CI 15·5–28·9) with gemcitabine + rituximab. However, response and survival outcomes do not always correlate in NHL (Lee et al , ; Zhu et al , ; Mangal et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tumor size end points from tumor growth inhibition (TGI) model was used to link exposure and OS in exposure‐TGI‐OS models in an attempt to resolve the confounding effect by baseline prognostic disease marker 56–58 . The association between survival and a short‐term end point such as response rate 59–61 or TGI 58 has been shown in some indications, but more work needs to be done in this direction.…”
Section: Strategies To Mitigate the Confounding Effectmentioning
confidence: 99%
“…Although PFS and OS are considered to be better pri-mary endpoints for efficacy analysis, CR and ORR are increasingly being used as surrogate endpoints in hematological oncology, as they can be measured in a shorter time. A meta-analysis by Mangal et al concluded that both ORR and CR rates were found to predict median PFS, indicating the potential of these endpoints to make timely decisions in developing new NHL therapies 40) . In our analysis, median PFS and OS for NHL were reported in three studies.…”
Section: Discussionmentioning
confidence: 99%